The Philosophy and History of the Moral ‘Ought’: Some of Anscombe’s Objections - Irwin, Terence (Ethical theory and moral practice, 2024)
According to G.E.M Anscombe’s paper ‘Modern Moral Philosophy’, modern moral philosophy has introduced a spurious concept of moral obligation, and has therefore made a mistake that the Greeks, and Aristotle in particular, avoided. Anscombe argues that the modern concepts of obligation, duty, and the moral ‘ought’ are the remnants of an earlier, but post-Aristotelian conception of ethics, and that they ought to be abandoned. An examination of Anscombe’s historical and philosophical claims shows that we have no reason to take them seriously. In particular, they rest on a misinterpretation of Scholastic views on ‘ought’ and obligation.